Effect of Ginger (Zingiber officinale) on Heavy Menstrual Bleeding: A Placebo‐Controlled, Randomized Clinical Trial. (8th October 2014) - Kashefi, Farzaneh; Khajehei, Marjan; Alavinia, Mohammad; Golmakani, Ebrahim; Asili, Javad
<x xml:space="preserve">Abstract</x> Objective: A wide range of herbal plants have been reported to treat various gynecological problems of women. This study was set out to investigate the effect of ginger (Zingiber officinale) on heavy menstrual bleeding (HMB) in high school girls. Methods: Ninety‐two young women who experienced HMB and met the inclusion criteria were recruited in this study. Participants were evaluated for six consecutive menstrual cycles. During 3 assessment cycles, their HMB was confirmed by Pictorial Blood Assessment Chart. They were then randomly allocated to two study groups to receive either ginger or placebo capsules. The participants filled in the same chart during three intervention cycles. Results: The level of menstrual blood loss dramatically declined during the three intervention cycles in ginger‐receiving group. The decrease of blood loss in ginger‐receiving group was significantly more remarkable than that of participants receiving placebo (p < 0.001). Minimum number of participants reported adverse effects. Conclusion: HMB is highly prevalent among young women. Considering the significance of appropriate and timely treatment and also the importance of prevention of unwanted consequences, ginger may be considered as an effective therapeutic option for HMB. Copyright © 2014 John Wiley & Sons, Ltd.